Ritus Ibadah Haji dalam Pandangan Mohammed Arkoun (Kajian Q.S al-Hajj[22]: 25-37) - Muhammad Sultan Latif (Jurnal Penelitian, 2020)
Mohammed Arkoun is a contemporary Muslim philosopher who has tried to offer several methods of interpreting al-Qur'an text so that it can produce an objective meaning.  In the understanding of the researcher, Arkoun offers three stages in exracting the meaning of the al-Qur'an text. Namely, first: take a linguistic approach. Second, understand the language of mystical structures. Third, the reach and boundaries of traditional exegesis. One of the themes studied by Arkoun was the pilgrimage. In Arkoun's view, the hajj ritual was different from other Muslim philosophers. He tries to understand the pilgrimage by looking all of the aspects and complements involved so that it can substantially redefine the pilgrimage itself. Arkoun does not only read verses related to Hajj as a mandatory and absolute commands from the almighty. With all the complexities of these components of worship, it should have an important meaning that Muslim philosopher in general have not heard so far. The meaning of Hajj in Arkoun's view is that Hajj is just not a departure from one place to another, but an act of transference of the soul from a bad soul to be better soul, from bad customs and habits to good customs and habits, as well as becomig the soul is more obedient and obedient to God.